THE ROLE OF STRATEGIC PIONEER ON ACHIEVING ORGANIZATIONAL INNOVATION A FIELD STUDY ON MINISTRY OF ECONOMY AND PLANNING EMPLOYEESIN KINGDOM SAUDI ARABIA - Al- Besisi, Ghalia Mohamad; Al- Shamassi, Areej Abdul Rahman (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the role of the dimensions of strategic Pioneer represented in (initiative, Pioneer mind, risk tolerance, flexibility, vision, growth) in achieving organizational innovation among the employees of the Ministry of Economy and Planning and knowledge of the level. Strategic Pioneer in the ministry, knowing the level of organizational innovation practice in the ministry, and knowing the trends of the sample members about the relationship between strategic Pioneer and organizational innovation due to demographic variables, the study problem was the question.: What is the role of strategic Pioneer in achieving organizational innovation? Strategic Pioneer and organizational innovation by studying together and practical by providing a scientific basis stemming from organizations wishing to apply the two concepts. An analytical questionnaire containing (61) items was designed as a tool for data collection, and the study population consisted of all 500 employees of the Ministry of Economy and Planning, and a simple random sample was selected from the study population, which numbered (150) employees, and the data was processed statistically using the two programs (SPSS). ) (AMOS). The results included: a statistically significant effect of risk tolerance (59.5%), which represents the largest proportion of the dimensions under study, followed by growth of (57.7%), then the succession of flexibility, pioneering mind, vision, and initiative. The study recommended a number of recommendations, including: giving the employee limits through which he can solve problems, as well as training courses that arise for employees. Pioneer skills development.